(untitled) (Swiss Medical Weekly, 2011)
Since the publication in 2009 of clinical practice guidelines for the management of hepatitis B virus (HBV) infection by the European Association for the Study of the Liver (EASL), a wealth of new data has emerged regarding the antivirals most commonly used to treat chronic hepatitis B. This review will summarise the most recent knowledge on these drugs, and how this may affect current and future management of HBV infection. Despite the progress in drug development, HBV infection remains a complex entity, characterised by a peculiar interplay between host and viral factors. With the potent drugs currently available, however, its management and control are possible in the majority of cases.